The "double identity": navigation of maternal and career identities in partnered, career-driven mothers - Premjith, Kimona (My University, 2021)
Research on mothers, specifically working mothers, is predominantly quantitative in nature and child-centered. The current research aimed at understanding the lived experiences of working mothers through their constructions and meaning-making of 'maternal identity', 'working identity' and how these two equally demanding identities have come to be navigated. The sample consisted of six working mothers with varying racial and cultural backgrounds. These women ranged from their mid to late thirties and were all married with at least one child between the ages of 2-11 years old. Of the six women, five had daughters whilst one mother had sons. This research was qualitative in nature and applied an interpretivist phenomenological framework. The research was carried out through semi-structured face-to-face interviews. The results yielded a blurring of the maternal and work identity, suggesting the intertwined nature of these identities. ‘Working identity’ was found to be a primary identity for most of these women as it afforded them independence and a sense of a self-made self. ‘Maternal identity’was found to be all consuming and a drastic change for many of these women, as they negotiated the loss of an old self with the gaining of a new maternal self. The intergenerational transmission of maternal identity featured prominently in how these women came to understand themselves as mothers. This was further influenced by both cultural and gender discourses alike, which permeated both the maternal and the work self, resulting in feelings of guilt, judgement and pressure. Through navigating these two identities, these women understood the importance of support and explored coping strategies aligned with that. These strategies included outsourcing elements of motherhood, using feedback and building a 'mom tribe'-a network of working mothers. Despite the challenging journey of being a working mother, these women were constructing their paths in their own ways, becoming the working mothers they wished to be grounded on their own personal histories and conceptions of motherhood. Thus, leading the research to conclude that motherhood is ever evolving and intersubjective
A dissertation presented in partial fulfilment of the requirements for the degree of Master of Arts in Clinical Psychology, University of Witwatersrand, 2021